Current development of satellite communications technology - GAN Zhong-min; ZHANG Geng-xin (Tongxin xuebao)
A summary and review about some hot points in current satellite communications technology was given.Firstly,the associated concept and developments of broadband satellite communication were introduced,then the main technical issues that need to be solved was proposed,and examples of the typical application were given.Secondly,based on the introduction of current developments about mobile satellite communication,the characteristics and key technology were studied.Finally,the basic concept of space communication network was introduced,the network composition and individual function were given,and some new technology that need to be developed was analized.